1, 3, 5‐Trichloro‐2, 4, 6‐Trinitrobenzene: The Elusive Impurity Standard. Issue 4 (7th February 2021) - Kelly, Kristin; Brown, Geoff
Abstract: 1, 3, 5‐triamino‐2, 4, 6‐trinitrobenzene (TATB) is an insensitive high explosive synthesized in two steps; 1, 3, 5‐trichloro‐2, 4, 6‐trinitrobenzene (TCTNB) is the only intermediate. Due to solubility limitations, TATB is often dissolved in dimethylsulfoxide (DMSO) for liquid chromatography‐mass spectrometry (LC–MS) analyses; however, DMSO is capable of participating in a wide variety of reactions. Intending to use it as an impurity standard, TCTNB was dissolved in DMSO. A stark color change from colorless to yellow accompanied by wavelength and ion chromatogram changes occurred over 24 hours. Three compounds were identified as causing the color change. All three were present in both acetone and DMSO solutions, but, overtime the absorbance spectra of the DMSO solution changed indicating an underlying reaction occurs between these compounds and DMSO. The chemical formulas of impurities present in the TCTNB sample as well as reaction products are identified via quadrupole time of flight mass spectrometry. The chemical structures are also proposed. The combination of the solvent system, ionization technique, and halogenated/nitrated aromatic ring structures resulted in substitutions of both the chlorine and nitro groups to hydroxyl groups. Three proposed structures were closely related to TCTNB, but only one was detected at a consistent mass and absorbance wavelength in both acetone and DMSO. This compound had undergone a chlorine to hydroxyl substitution and should be utilized for TCTNB detection. Abstract :